Determinación del perfil lipídico en pobladores del sector La Merced del distrito El Porvenir. 2008”. - Rodríguez Del Aguila, Melisa Rosa Luz (2009)
Diverse investigations have established a relationship between an altered lipid profile and higher risk of cardiovascular diseases, which have their highest incidence in adult people. 106 individuals (40 men and 66 women) over 24 to 65 years of age and from La Merced sector of El Porvenir district were chosen at random order. They were divided by age groups (25-44 years and 45-65 years) and by gender. Serum concentrations of total cholesterol (TC), Triglycerides (TAG) and HDL-c were determined; the Friedwald formulas were used for the remaining fractions. TC (mg/dl) showed a significant difference in relation with each age gender (195.5±18.7mg/dL Vs 206.9±18.3mg/dL). Tryacilglicerides (mg/dl) showed difference between men age groups (197.4±25.5mg/dL Vs 169.6±21.8mg/dL). HDL-c (mg/dl) levels showed differences according to sex in all age groups, 25-44a (39.7±2.1mg/dL-H Vs 46.0±2.9mg/dL-M), 45-65a (41,3±3.6mg/dL-H Vs 43.4±2.7mg/dL-M). LDL-col (mg/dl) concentrations showed difference in each of the men’s age groups (116.4±17.7mg/dL Vs 131.7±19.5mg/dL). The study showed Triglycerides levels increased as age increase, likewise there were significant differences in the HDL-c levels between sexes for all age groups studied